Upaya Peningkatan Output Aktual di Line 2 Finishing - Chandra, Anthony; Yang Aysia, Debora Anne (Jurnal Titra, 2015)
PT. Integra Indocabinet is a wood furniture company. The company produces two types of products which are set-up product and knockdown product. Each product has monthly target which is set by PPIC department, which is 70 containers per month for knockdown type. However finishing department canât fulfill this target. The purpose of this research are giving evaluation of actual output in finishing department, and suggesting several ways to improve the actual output. Observation, interview and time study are several methods which are used in this research. Observation and interview methods are used to find the root causes of the problem and to collect the historical data. Stopwatch time study is used to obtain the production capacity at finishing department. The result of production capacity calculation is 64.72 containers, while the actual output is only 62 containers. These capacity value and actual output value are not compatible with PPIC target, which are 70 containers. There are several factors which caused the actual output in finishing department is not optimum, they are the quantity and quality of the raw material from sanding department, higher occurrence of paint replacement, and many defect of WIP components. There are several improvements which are suggested to increase the actual output value. They are utilization of deadline form, classification of similar product in order to reduce the occurrence of paint replacement, and pallet modification to prevent WIP component fell down during production process.